Efektivitas Promosi dan Keragaman Produk terhadap Keputusan Pembelian Konsumen - Aufa Nakia Chayyu Ashiil; Idah Kusuma Dewi (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2026)
This study aims to analyze the influence of promotion and product diversity on consumers’ purchasing decisions at the culinary business Lika Liku Semarang. Increasingly intense competition in the culinary industry requires business actors to develop effective marketing strategies. The research employs a quantitative approach, with data collected through questionnaires distributed to consumers of Lika Liku Semarang. Data analysis was conducted using multiple linear regression to examine the effects of the independent variables on the dependent variable. The results indicate that promotion has a positive and significant effect on purchasing decisions. Meanwhile, product diversity does not have a significant effect on purchasing decisions. However, simultaneously, both variables have a significant influence on purchasing decisions. These findings suggest that promotional strategies are the dominant factor in driving consumers’ purchasing decisions, while product diversity functions as a supporting factor that complements the attractiveness of promotion.